2019
DOI: 10.1177/0011128719875699
|View full text |Cite
|
Sign up to set email alerts
|

Public Opinion on Criminal Records and Employment: A Test of Competing Theoretical Models

Abstract: Much prior research has examined the sources of individuals’ attitudes toward the application of punishment via the justice system. Some findings from this literature suggest that punitive attitudes are expressive, retributive, and closely connected to racial resentment. Other research, however, emphasizes that these sentiments are instrumental, utilitarian, and associated with the management of perceived risk. To date, little research has explored public attitudes regarding employment as a reentry barrier, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 114 publications
(221 reference statements)
3
25
0
Order By: Relevance
“…DeWitt and Denver (2020) showed that the public is more supportive of hiring people with records, even violent felony records, when they have positive credentials, such as a supportive reference letter. Lehmann, Pickett, and Denver (2020) found that instrumental, risk-related concerns, such as perceived recidivism risk, played a stronger role than retributive factors in public opinion about hiring people with criminal records. And Lageson et al (2019) found that perceived recidivism risk increased support for allowing private companies to publicize criminal records online.…”
Section: Public Support For Expungement: Risk and Redeemabilitymentioning
confidence: 94%
See 4 more Smart Citations
“…DeWitt and Denver (2020) showed that the public is more supportive of hiring people with records, even violent felony records, when they have positive credentials, such as a supportive reference letter. Lehmann, Pickett, and Denver (2020) found that instrumental, risk-related concerns, such as perceived recidivism risk, played a stronger role than retributive factors in public opinion about hiring people with criminal records. And Lageson et al (2019) found that perceived recidivism risk increased support for allowing private companies to publicize criminal records online.…”
Section: Public Support For Expungement: Risk and Redeemabilitymentioning
confidence: 94%
“…Collectively, these findings lead us to hypothesize that the public will support expungement most when records are old or are limited to juvenile offending, are for nonviolent offenses, and are counterbalanced by rehabilitation signals, such as positive credentials. Given the public's general opposition to record-based stigmatization (Lageson et al, 2019), and its belief that employment reduces reoffending (Lehmann et al, 2020), we also expect the public will support efforts to ensure the accuracy of any available criminal record information.…”
Section: Public Support For Expungement: Risk and Redeemabilitymentioning
confidence: 99%
See 3 more Smart Citations